2016
DOI: 10.5513/jcea01/17.4.1840
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the physicochemical quality indicators of Musculus Longissimus Dorsi from Mangalitsa Breed and their crossbreeds

Abstract: In recent years, there has been a current trend in the market of pork to create products based on traditional, regional specialities, where is used technology such as drying, smoking and fermentation of products. These products require a specific quality of meat from pure-bred indigenous breeds or their crossbreeds with emphasis on dry matter content, intramuscular fat content in meat and fatty acid composition with higher share of unsaturated fatty acids and essential fatty acids. Due to this fact, indigenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As reported by Kasprzyk [ 11 ], Babicz [ 14 ], and Wojtysiak and Połtowicz [ 15 ], this creates a possibility of using Pulawska pigs for producing brand-name products, e.g., Pulawska ham. Bocian et al [ 16 ], Debrecéni et al [ 17 ], Matoušek et al [ 18 ], and Colonna et al [ 19 ] claimed that native breeds are raised for culinary meat and that the interest in products made traditionally is greater in the United States and some European countries e.g., Hungary, Switzerland, Austria, Germany, Spain, Great Britain, and Poland. Studies [ 9 , 14 ] have demonstrated that good-quality pork can be obtained by crossbreeding native and commercial breeds.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Kasprzyk [ 11 ], Babicz [ 14 ], and Wojtysiak and Połtowicz [ 15 ], this creates a possibility of using Pulawska pigs for producing brand-name products, e.g., Pulawska ham. Bocian et al [ 16 ], Debrecéni et al [ 17 ], Matoušek et al [ 18 ], and Colonna et al [ 19 ] claimed that native breeds are raised for culinary meat and that the interest in products made traditionally is greater in the United States and some European countries e.g., Hungary, Switzerland, Austria, Germany, Spain, Great Britain, and Poland. Studies [ 9 , 14 ] have demonstrated that good-quality pork can be obtained by crossbreeding native and commercial breeds.…”
Section: Introductionmentioning
confidence: 99%